Cultivo de yuyo "Chondracanthus chamissoi" - Huamán Arones, Klever Eduardo (2024)
El objetivo de este trabajo es transmitir la técnica de cultivo de Chondracanthus chamissoi, basada en la capacidad de esta alga de reproducirse mediante discos de fijación secundaria, que le confieren propiedades únicas para incrementar la biomasa mediante métodos sencillos. Bajo costo en comparación con la tecnología de rastreo. El cultivo comercial de Chondracanthus chamissoi radica en el alto valor que se obtiene de este recurso, que tiene una importante demanda para consumo humano en los países asiáticos, pero aún no se ha aprovechado plenamente esta oportunidad de negocio porque no se han logrado los estándares de calidad necesarios. Falta de suministro constante de materias primas para los exportadores. Dadas las características de la alternativa tecnológica propuesta, se busca poner esta tecnología a disposición de comunidades pesqueras amateurs interesadas en las condiciones marinas para iniciar el cultivo de Chondracanthus chamissoi. ----- Macroalgae are an important economic resource and a key element of the ecosystem. In recent years, there has been an overexploitation of the resource by increasing the demand of the food industry. The present work aims to disseminate a technique of cultivation of Chondracanthus chamissoi based on the ability of this alga to reproduce by secondary fixation discs (DFS), which gives it a unique characteristic to increase its biomass using a simple technique And low cost, compared to the spore technique. The interest Commercial of the cultivation of Chondracanthus chamissoi lies in the high values achieved by this resource, which has a significant demand in the human consumption of Asian countries, business opportunity that is not being fully exploited because the required quality standards are not met and the lack of permanent supplies of raw material to exporters. Given the characteristics of the technological alternative presented is intended to make available to communities of artisanal fishermen who have the interest and the sea conditions technology to begin with the cultivation of Chondracanthus chamissoi.